GREEN ENERGY IS THE PILLAR OF THE FUTURE - Yulchiev M.E.,; Qurbanboyev Abdujalil Murotjon o'g'li,; Shamsiddin Hakimboy o‘g‘li, (Лучшие интеллектуальные исследования, 2024)
Abstract: In this article, the main issue is the energy crisis in the field of energy today, environmental and social problems are thoroughly studied, and in the future, we will focus on the types of energy called green energy that does not pollute the atmosphere by reducing environmental waste. The author focused on the opinions on hydrogen energy, its storage, production and use, which is currently supported by many countries. The article also talks about the expected energy future of the World Energy Organization in the next 30 vears.